A comparison of nitrate removal and denitrifying bacteria populations among three wetland plant communities. Issue 1 (20th February 2020) - Gordon, Brad A.; Lenhart, Christian; LaPara, Timothy M.
Abstract: Reed canary grass ( Phalaris arundinacea L.) is an invasive, cool‐season grass commonly dominating wetlands with high nutrient loads. Its impact on nitrogen removal via denitrification in wetlands is unknown. Most studies of denitrification in treatment wetlands have focused on the effects of physical or chemical variables and not on the effects of plant roots on the soil environment. The purpose of this study was to measure effects of plant type on denitrification rates in typical wetland soils of the midwestern United States by comparing wet prairie mix, switchgrass‐dominated, and reed canary grass plant communities. Nitrate (NO3 − ) removal and other parameters were measured in miniature wetlands, or mesocosms, containing each plant community transplanted from a small agricultural treatment wetland in southern Minnesota. Quantitative polymerase chain reaction analysis was used to quantify the total bacteria population (measured with 16S rRNA genes) and denitrifying gene abundance (measured with nosZ genes) from the rhizosphere of each plant community. The wet prairie mix mesocosms on average removed the most NO3 − in each test ( p  = .01 and .08). Whereas the wet prairie mix removed the most NO3 − from the surface water ( p  < .01), reed canary grass removed more from the subsurface ( p  < .01). Ratios of denitrifying to total bacteria were higher in the wet prairie mix than in the other communities' root zones ( p  < .05). Results suggest that reed canary grass invasion could reduce denitrification in wetlands, especially during the spring and fall when it is growing but other plants are dormant.